Enhanced N2‐fixation and NH4+ recycling during oceanic anoxic event 2 in the proto‐North Atlantic - I. Ruvalcaba Baroni; I. Tsandev; C. P. Slomp (Geochemistry, Geophysics, Geosystems)
Abstract Evidence from sediment core records and model studies suggests that increased nutrient supply played a key role in the initiation of the Cenomanian‐Turonian oceanic anoxic event 2 (OAE2; 94 Ma). However, the relative roles of nitrogen (N) and phosphorus (P) availability in controlling primary productivity during the event are not fully understood. Here we expand an existing multibox model of the coupled cycles of P, carbon, and oxygen in the proto‐North Atlantic by adding the marine N cycle. With the updated version of the model, we test the hypothesis that enhanced availability of P can fuel N2‐fixation, increase primary productivity and drive large parts of the proto‐North Atlantic to anoxia during OAE2. In a sensitivity analysis, we demonstrate that N dynamics in the proto‐North Atlantic respond strongly to variations in oxygen and P supply from the Pacific Ocean and to changes in circulation. The implemented N cycle weakly modifies the carbon cycle, implying that P was the major nutrient controlling primary productivity during OAE2. Our model suggests that both N2‐fixation and upwelling of recycled NH4+ were enhanced during OAE2 and that N2‐fixation was the major source of N in the proto‐North Atlantic. Denitrification was more important in the water column than in sediments, with high rates in the open ocean and in the Western Interior. High P inputs in the proto‐North Atlantic led to widespread N2‐fixation, which more than compensated for the loss of N through denitrification. As a consequence, rates of primary productivity and organic carbon burial were high.